Pelatihan Mengoperasikan Microsoft Office Pada Siswa-Siswi SMPN Satu Atap Pesawaran - Hendra Kurniawan; Sushanty Saleh; Sri Karnila; Neni Purwati; Nurjoko Nurjoko; Egi Safitri; Ruki Rizal (Institut Informatika dan Bisnis Darmajaya, 2023)
This community service aims to provide insight and knowledge to students on SMPN Satu Atap how to operate Microsoft Office so that students' ability to use Microsoft Office can be used to assist or support academic activities at school by providing training. The implementation of this service is completed in three stages of activity, namely preparation, implementation, reporting. Preparation is done by conducting a preliminary survey to find out what students need to support teaching activities in class. The training was carried out using the lecture method, namely the presentation technique, followed by direct practice assisted by the team, accompanied by questions and answers and exercises carried out by the training participants. This activity was attended by approximately 30 students, from 08.00-16.00 WIB for one day, taking place in classes of the SMPN Satu Atap. The final stage of this service is to report the results of the activities. The results of the activities that have been carried out by the students look very enthusiastic in following every material presented by the service team as evidenced by the activity between students and the service team.Keywords — Training, Microsoft Office, Students